Modul Dinamika Partikel Terintegrasi Permainan Tradisional Berbasis E-Learning untuk Meningkatkan Literasi Sains - Noly Shofiyah; Ria Wulandari; Enik Setiyawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This research is aimed to develop a particle dynamics module integrated traditional games that is applied in e-learning to improve scientific literacy skills. This study was a developmental research because it developed a module based on local wisdom with the R and D method developed by Borg and Gall. Research procedures included preliminary studies, product planning, product development, product validation (validation by experts), product revisions and field tests. Field trials used one group pretest-posttest design with 19 students of 4th natural science education as the samples. The instruments used were validation sheets and scientific literacy test. The results showed that the Particle Dynamics module based on local wisdom of traditional games was declared valid and feasible by experts to be implemented in distance learning (e-learning). In addition, the application of the particle dynamics module based on local wisdom of the traditional game through e-learning had a moderate effect on students' scientific literacy skills.